1994
DOI: 10.1061/(asce)0733-950x(1994)120:1(74)
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Solitary Wave Breaking Induced by Breakwaters

Abstract: ABSTRACT:Laboratory experiments are presented for the breaking of solitary waves over breakwaters. A variety of behaviors is observed, depending on both breakwater and incident wave height: for emerged breakwaters, waves may collapse over the crown, or break backward during rundown; and for submerged breakwaters, waves may break forward or backward, downstream of the breakwater. The limit of overtopping and wave transmission and reflection coefficients are experimentally determined. It is seen that transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…Due to their simplicity as compared to periodic waves, solitary waves have often been used for both model development and experimental validation. Grilli et al [12,13,[15][16][17], for instance, showed that the shape of shoaling and breaking solitary waves propagating over a step, a submerged trapezoidal obstacle, or a slope, could be simulated within a few percent of experimental measurements in a 2D-BEM-FNPF-NWT. Similar validations were repeated in 3D, e.g., by Grilli et al [11].…”
Section: Fully Nonlinear Potential Flow In a Bem Formulationmentioning
confidence: 99%
“…Due to their simplicity as compared to periodic waves, solitary waves have often been used for both model development and experimental validation. Grilli et al [12,13,[15][16][17], for instance, showed that the shape of shoaling and breaking solitary waves propagating over a step, a submerged trapezoidal obstacle, or a slope, could be simulated within a few percent of experimental measurements in a 2D-BEM-FNPF-NWT. Similar validations were repeated in 3D, e.g., by Grilli et al [11].…”
Section: Fully Nonlinear Potential Flow In a Bem Formulationmentioning
confidence: 99%
“…Free surface elevations are compared with those by Grilli et al [18] which are based on fully nonlinear potential flow equations. Computational domain is illustrated in Figure 3.…”
Section: Propagation Of Solitary Wave Over a Submerged Breakwatermentioning
confidence: 99%
“…For further evaluation of SPH accuracy, the free surface profile, generated in solitary wave-breakwater interaction, is compared with experimental work of Grilli et al [33]. To perform this comparison, a computational domain is defined (Table 1).…”
Section: Validationmentioning
confidence: 99%